2017
DOI: 10.1007/s00264-017-3491-5
|View full text |Cite
|
Sign up to set email alerts
|

Results of arthroscopic Bankart repair with Hill-Sachs remplissage for anterior shoulder instability

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…20,21,35,38,51,83 e Arthroscopic soft tissue and remplissage. 9,10,12,25,34,54,58 f Open soft tissue. 3,11,44,59,72,74,77 g Hardware problems: problems involving screw or anchor breaking; screw removal, exchange, or malposition; and coracoid drilling or fixing problems. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21,35,38,51,83 e Arthroscopic soft tissue and remplissage. 9,10,12,25,34,54,58 f Open soft tissue. 3,11,44,59,72,74,77 g Hardware problems: problems involving screw or anchor breaking; screw removal, exchange, or malposition; and coracoid drilling or fixing problems. …”
Section: Resultsmentioning
confidence: 99%
“…Following quality assessment with the MINORS criteria, 71 the noncomparative studies had a mean score of 12.2 (range, [8][9][10][11][12][13][14] and comparative studies, 18.5 (range, 7-24). Table 1 provides a breakdown of these scores for each surgical procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the studies, the association of Bankart and Hill-Sachs lesions is common (3,16,17). In their study, Widjaja et al (3) showed a significant correlation between the incidence of Bankart and Hill-Sachs lesions and that the incidence of one lesion increased the incidence of the other 2.67 times.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies on patients with BR with reported postoperative decreases in ROM have shown that the loss was significant compared with ROM at preoperative assessment or on the contralateral side. 2,4,20,21 A systematic review on post-BR outcomes 30 found that 5 of 9 (55.6%) articles reported significant postoperative limitations ( P < .05) in multidirectional ROM compared with ROM at preoperative assessment or on the contralateral side, with the most common loss seen in ER 0 at 9° to 14°. 1,12,18,37,59 Other reports have included 1° to 16° in ER 90 loss 1,18 and 8° to 10.8° in FF.…”
Section: Discussionmentioning
confidence: 99%